2023
DOI: 10.1021/acsami.2c20930
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Janus MXene Inks for Versatile Functional Coatings on Arbitrary Substrates

Abstract: Solution processing of two-dimensional nanomaterial inks guarantees efficient, straightforward fabrication of functional films, coatings, flexible devices, etc. Despite the excellent solution processibility and viscoelasticity of MXene aqueous inks, formulation of nonaqueous MXene inks with great affinity to both hydrophilic and hydrophobic substrates has proven quite challenging, limiting the practical applications of MXenes in printing/coatings on various substrates. Here, MXene surface chemistry is manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…On the one hand, the surface functional groups of MXenes can be used as the reaction platforms to chemically modify the MXene materials. For example, Chen et al synthesized novel Janus MXene nanosheets through manipulation of the MXene surface chemistry by asymmetrically grafting polystyrene onto the MXene nanosheets . The modified MXene nanosheets achieve hydrophilicity on one side and hydrophobicity on the other.…”
Section: An Overview Of Mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the surface functional groups of MXenes can be used as the reaction platforms to chemically modify the MXene materials. For example, Chen et al synthesized novel Janus MXene nanosheets through manipulation of the MXene surface chemistry by asymmetrically grafting polystyrene onto the MXene nanosheets . The modified MXene nanosheets achieve hydrophilicity on one side and hydrophobicity on the other.…”
Section: An Overview Of Mxenesmentioning
confidence: 99%
“…For example, Chen et al synthesized novel Janus MXene nanosheets through manipulation of the MXene surface chemistry by asymmetrically grafting polystyrene onto the MXene nanosheets. 85 The modified MXene nanosheets achieve hydrophilicity on one side and hydrophobicity on the other. Hence, this fascinating asymmetric wettability enables stable dispersion of the Janus MXene in various organic solvents ranging from polar to nonpolar, effectively expanding the application area of MXenes, especially in nonaqueous systems.…”
Section: Photothermal Conversionmentioning
confidence: 99%
“…Abundant surface functional groups provide MXene with excellent dispersibility in water and organic solvents, allowing the use of Ti 3 C 2 T x in a multitude of sensor applications. [ 28–31 ] 4) Good biocompatibility for biosensors. Unal et al.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant surface functional groups provide MXene with excellent dispersibility in water and organic solvents, allowing the use of Ti 3 C 2 T x in a multitude of sensor applications. [28][29][30][31] 4) Good biocompatibility for biosensors. Unal et al [32] demonstrated the high biocompatibility of MXenes by studying MXenes with antiviral and immunomodulatory properties against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Janus structures in two-dimensional (2D) materials are distinguished by their asymmetric vertical stacking with unique surface compositions, disrupting vertical symmetry and giving rise to novel physical–chemical phenomena. , For instance, Janus structures can be created by structural modifications within established classes of 2D materials, which includes transition-metal dichalcogenides (TMDs), MXenes, monochalcogenides, or any other 2D materials comprised of a few layer thickness. The symmetry breaking in the vertical direction is a key point that gives rise to numerous applications in the scope of semiconductor optoelectronic devices with prospects for applications as sensors, photocatalytic water splitting materials, functional coatings, and so on.…”
Section: Introductionmentioning
confidence: 99%